Transfemoral amputation for the treatment of anemia and unfavorable evolution of left lower limb infection with a wound infected by Klebsiella oxytoca – Case report - Dias , Miguel A.; Thomé , Henrique I. (Seven Editora, 2023)
Objective: to report the case of a patient who underwent a transfemoral amputation for the treatment of anemia and unfavorable evolution of left lower limb infection with a wound infected by Klebsiella oxytoca. Method: the information was obtained through a review of the medical record, an interview with the patient, laboratory results, and a literature review. Conclusions: The reported case and the scarcity of the literature bring to light the discussion on the pathogenicity of Klebsiella oxytoca. However, the evidence that the transfemoral amputation of the limb that presented the eschar contaminated with Klebsiella oxytoca, led to the cure of chronic anemia and the cessation of bloody diarrhea, confirms that the decision made resulted in curative treatment and improved the patient’s quality of life. DOI:https://doi.org/10.56238/alookdevelopv1-053